Clinical analysis and comparative study of facial symmetry of three-dimensional skull models. - Zhengrui Zhang; Aijia Deng; Hao Li; Yunming Li; Jianhua Wei; Yan Wang (PLoS ONE)
Facial symmetry is a critical determinant in maxillofacial reconstruction. To establish an ideal midsagittal plane (MSP) for three-dimensional (3D) skull model in the diagnosis and treatment of maxillofacial reconstructing and unilateral maxillofacial lesions, the maxillofacial spiral computed tomography data from 51 patients with normal craniofacial anatomy in the Department of Stomatology, The General Hospital of Western Theater Command, Chengdu, Sichuan Province, China, were collected to performed 3D reconstruction. Every 3D skull model established three common MSPs: N-ANS-PNS, N-ANS-S, and N-Ba-S by corresponding anatomical landmarks. The original 3D skull models were mirrored using different MSPs to construct mirror models. The MSPs accuracy was assessed through repeated measures analysis combined with the 3D chromatic deviation mapping. Quantitative comparisons revealed statistically significant differences (P < 0.05) in overlap precision across MSP definitions. Mean deviation values (± SD) between the mirror and original models of N-ANS-PNS, N-ANS-S, and N-Ba-S were -1.1415 ± 0.6651, -0.9075 ± 0.6279, and -0.3961 ± 0.7970 mm respectively. Gender-based analysis demonstrated significantly better facial symmetry in female models compared to males across all MSP definitions (P < 0.05), while demographic factors (age, height, and weight) showed no statistically significant correlation with symmetry outcomes (P > 0.05). These findings validate the efficacy of mirroring technology combined with 3D chromatic deviation mapping for MSP accuracy assessment. The N-ANS-PNS plane emerged as the most reliable reference for facial symmetry evaluation in 3D skull models, with female morphology exhibiting inherently superior bilateral symmetry compared to male counterparts.